Comparing Methods and Finding H. pylori Infections and their Resistance to Beta Lactam Drugs as Seen in Peshawar, Pakistan (Journal of Basic and Applied Research in Biomedicine, 2022)
The aims of this study were to find and report pattern of resistance towards beta lactam antibiotics in patients infected with H. pylori by visiting Hayatabad Medical Complex (HMC). Diagnostic procedures like: gastroendoscopy, Rapid Urease Test (RUT), biochemical testing, microscopic examination, antibacterial sensitivity tests and molecular methods were utilized and compared. Polymerase chain reaction was used to find 16S rRNA gene fragment. Hundred forty-four patients were found H. pylori positive for urease and 182 were positive for catalase. Hundred and thirty-two were positive for oxidase while hundred eighty were Gram negative. By polymerase chain reaction, 16S rRNA gene fragment was found to be positive in 164 subjects. The pattern of antibiotics resistance in H. pylori as seen in Peshawar, Pakistan in 200 gastric biopsies. A poorer resistance level towards amoxicillin is noticeable as due to low socioeconomic conditions.